Perancangan Sistem Antrean Berbasis Web Apotek Veteran Menggunakan ERD, CDM, PDM - Adiva Mayyadah Putri Prasetyo; Khansa Khayyira Kurniawan; Rania Lionar; Zatin Niqotaini (GLOBAL SCIENTS PUBLISHER, 2026)
Digital transformation in healthcare requires improving queue management and drug inventory in pharmacies. A major problem in traditional pharmacies is patient crowding, which stems from uncertainty about waiting times and drug availability. This study seeks to create a web-based Queue Information System for Veteran Pharmacy that includes real-time queue tracking and clear drug status updates. The system will mainly show the status of prescription processing; when stock runs out, the status will change to restocking. This allows patients to leave the pharmacy and receive automatic notifications when their medicine is available, cutting down on physical waiting time. The methodology emphasizes structured database design using the Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM) approaches for implementation in a Database Management System (DBMS). The results outline a plan for a web application that effectively reduces waiting room congestion and speeds up the drug supply process through automated restocking.